A Synthesis of Peer-Mediated Academic Interventions for Secondary Struggling Learners. (September 2015) - Wexler, Jade; Reed, Deborah K.; Pyle, Nicole; Mitchell, Marisa; Barton, Erin E.
A synthesis of the extant research on peer-mediated reading and math interventions for students in regular or alternative education settings with academic difficulties and disabilities in Grades 6 to 12 (ages 11–18) is presented. Interventions conducted between 2001 and 2012 targeting reading and math were included if they measured effects on at least one academic outcome measure. A total of 13 intervention studies were synthesized in which 10 studies employed an experimental or quasi-experimental design and three studies used a single-case design. Findings from the 13 studies revealed mostly moderate to high effects favoring peer mediation, particularly when implementing a peer-mediated feedback component. In addition, findings suggest such interventions have social validity among adolescents and teachers. More rigorous research on secondary peer-mediated math interventions, peer-mediated interventions in alternative settings, and effective ways to pair dyads to incorporate a structured feedback component is warranted. Implications for peer-mediated instruction for academically struggling adolescents are discussed.